CGIAR Initiative on Low-Emission Food Systems (Mitigate+) supports the international forum of low-emission agrifood systems launched in Beijing - Song, Ziqian (Initiative on Low-Emission Food Systems, 2023)
On July 4, 2023, the launch meeting of the International Forum of Low-emission Agrifood Systems (IFLEAS), jointly initiated by China Agricultural University, the CGIAR Research Initiative on Low-Emission Food Systems (Mitigate+), and the Beijing Representative Office, was held in Beijing. Xin Xian, vice president of China Agricultural University; Qian Keming, research fellow of the Chinese Academy of Agricultural Sciences and former vice minister of commerce; Qin Hu, vice president and chief representative of the Beijing Office of EDF, delivered the opening speeches.